2016
DOI: 10.1016/j.scitotenv.2016.01.154
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and risk of cardiovascular hospitalization: An updated systematic review and meta-analysis

Abstract: The association between temperatures and risk of cardiovascular mortality has been recognized but the association drawn from previous meta-analysis was weak due to the lack of sufficient studies. This paper presented a review with updated reports in the literature about the risk of cardiovascular hospitalization in relation to different temperature exposures and examined the dose-response relationship of temperature-cardiovascular hospitalization by change in units of temperature, latitudes, and lag days. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
133
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(150 citation statements)
references
References 90 publications
12
133
3
2
Order By: Relevance
“…The literature generally suggests that exposures to both high and low temperatures are associated with cardiovascular events in non-pregnant populations around the world (Basu, 2009; Bhaskaran et al, 2012; Ha et al, 2014; Honda et al, 2016; Phung et al, 2016; Sartini et al, 2016; Wang et al, 2016; Yang et al, 2015) with potentially higher sensitivity among Blacks women, those with lower socioeconomic status, the elderly, and young children (Basu, 2009); but data among pregnant women are currently lacking. One large international multicenter case-control study among reproductive age women ages 15 to 49 showed that each 5°C decrease in monthly average temperature was associated with a 7% and 12% increase in hospital admission rates for stroke and acute myocardial infarction, respectively; and these effects were more prominent within one month of exposure (Chang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The literature generally suggests that exposures to both high and low temperatures are associated with cardiovascular events in non-pregnant populations around the world (Basu, 2009; Bhaskaran et al, 2012; Ha et al, 2014; Honda et al, 2016; Phung et al, 2016; Sartini et al, 2016; Wang et al, 2016; Yang et al, 2015) with potentially higher sensitivity among Blacks women, those with lower socioeconomic status, the elderly, and young children (Basu, 2009); but data among pregnant women are currently lacking. One large international multicenter case-control study among reproductive age women ages 15 to 49 showed that each 5°C decrease in monthly average temperature was associated with a 7% and 12% increase in hospital admission rates for stroke and acute myocardial infarction, respectively; and these effects were more prominent within one month of exposure (Chang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Massive previous studies have linked cold weather with hospitalization and mortality from CVD (Kysely et al, 2009;Phung et al, 2016). But the precise pathophysiologic mechanisms of the impact of cold temperature on CVD remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cold has been worldwide associated with cardiovascular outcome (Kysely et al, 2009;Phung et al, 2016). Previous studies have observed increased risks of myocardial infarction (Bhaskaran et al, 2010), stroke (Fustinoni et al, 2013) and hypertension (Jansen et al, 2001) when temperature declines.…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews showed a weak effect of hot temperatures on cardiovascular diseases in the elderly [6], and in general population [10], but such effect was not found in a meta-analysis by Turner et al 2012 [9]. Another meta-analysis by Phung et al aligned [11] with Turner et al regarding the lack of effect of hot temperatures, but reported a positive association of heatwaves with cardiovascular hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme cold increases the risk of cardiovascular hospitalization not only during cold spells but also some days after the cold spell episode occurred [711]. Studies assessing the impact of cold spells on health have mainly been conducted in cold-weather regions of Russia [16], Canada [12], China [13], USA [14] and United Kingdom [15].…”
Section: Introductionmentioning
confidence: 99%